Bad News Travels Slowly: Size, Analyst Coverage, and the Profitability of Momentum Strategies - Hong, Harrison; Lim, Terence; Stein, Jeremy C. (Journal of Finance, 2000)
Various theories have been proposed to explain momentum in stock returns. We test the gradual‐information‐diffusion model of Hong and Stein (1999) and establish three key results. First, once one moves past the very smallest stocks, the profitability of momentum strategies declines sharply with firm size. Second, holding size fixed, momentum strategies work better among stocks with low analyst coverage. Finally, the effect of analyst coverage is greater for stocks that are past losers than for past winners. These findings are consistent with the hypothesis that firm‐specific information, especially negative information, diffuses only gradually across the investing public.